Negotiating In-Group and Out-Group Identities through Translanguaging in English Area Communities: Menegosiasikan Identitas Kelompok Dalam dan Kelompok Luar Melalui Translanguaging di Komunitas Berbahasa Inggris - Fadhlan Saini; Putu Kerti Nitiasih; Ni Made Ratminingsih; Ni Komang Arie Suwastini (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Along with the development of sociolinguistic studies and language education, the orientation of research and learning practices is shifting from a monolingual approach to a more inclusive multilingual framework. In this context, translanguaging is seen as a communicative practice that allows individuals to use the entirety of their linguistic resources dynamically to build meaning, form identity, and establish social relationships. Purpose: This study aims to explore the practice of translanguaging within English Area communities that function as Community of Practice (CoP), focusing on the role of such practices in strengthening social cohesion as well as in the identity negotiation process between core members and outsiders of the community. Method: This research applies ethnographic case study approach. Data collection was conducted through participatory observation, semi-structured interviews, and review of community documents involving various actors, ranging from core administrators, active members, new members, former members, to external observers. Data analysis was conducted using Thematic Analysis to reveal patterns of language use, linguistic norms that develop, and the dynamics of social identity formation in the community. Results and Discussion: Research findings show that the English Area acts as a community of practice that supports the collaborative and sustainable English learning process. The practice of translanguaging not only serves as a pedagogical strategy to facilitate the understanding of the material, but also as an effective strategy that contributes to decreasing language anxiety and increasing member engagement. The use of language in the community is flexible and situational, where English is applied in accordance with the goals of the activity and the level of readiness of the participants. Although the ability to speak English serves as a symbol of membership, the application of language flexibility actually strengthens the sense of community and reduces the potential for social exclusion. Conclusions and Implications: This study confirms that translanguaging plays an important role in language learning, identity formation, and the sustainability of communities of practice, and has implications for the development of more inclusive and contextual English learning practices.